The role of the administrative leadership in raising the motivation to work among the employees and its impact on the distinction of institutional performance in the General Administration of Education in Al-Jawf region - AL-Mufarj, Amani Turki Aied (Journal of Educational and Psychological Sciences, 2021)
The aim of the research is to identify the role of administrative leadership in raising motivation to work among employees and its impact on the excellence of institutional performance in teaching Al-Jouf, and the descriptive analytical approach and the questionnaire were used as a research tool, and the questionnaire consisted of (65) paragraphs distributed on two axes, and was applied to (210) Singles, which varied between (leader, teacher, educational supervisor, administrative assistant).And after analyzing the data statistically, the results came as follows: The statistical indicators showed that the degree to which leaders practiced their role in raising the motivation to work among the employees from the employees' point of view was a degree of agreement, and the average responses ranged between (3.40- 4.19).Among the most prominent phrases in the approval rate: The administrative leadership encourages employees to perform work well, the administrative leadership supports the professional growth of its employees.The research reached a set of recommendations, the most prominent of which are: Providing professional development opportunities for leaderships by providing quality internal and external training programs aimed at enhancing leadership skills to suit contemporary changes and challenges. Improving the preparation of second-grade leaderships programs and developing their leadership and creativity skills. Utilizing the proposed procedural methodology prepared by the researcher based on the (Claire) model to design motivation to work.
Keywords: Management leadership; motivation to work; institutional excellence